Deprivation and discovery motives determine how it feels to be curious. (October 2020) - Noordewier, Marret K; van Dijk, Eric
Highlights: Curiosity reflects motives to end knowledge deprivation and to discover new knowledge. These deprivation and discovery motives underlie affective components of curiosity. A deprivation motive evokes more negative feelings than a discovery motive. Individual, target, and information-gap features determine motivational strength. Abstract : Curiosity is evoked when people experience an information-gap between what they know and what they do not (yet) know. Curious people are motivated to find the information they are missing. This motivation has different components: People want to reduce the uncertainty of not knowing something (deprivation motive) and they want to discover new information to expand their knowledge (discovery motive). We discuss recent research that shows that the affective experience of curiosity is the result of the relative strength of the deprivation and discovery motives. This, in turn, is contingent on individual differences, anticipated features of the actual target, and features of the information-gap.